EFISIENSI DAN EFEKTIVITAS PENDISTRIBUSIAN ZAKAT FITRAH DI LAZ ALMADINA - Qurrotul Aini, Hana; Ayu Safitri, Intan; Adi Saputra, Moh. Juan; Aprilia Sari, Chusmawati; Sa'adah, Mazro'atus (Program Studi Manajemen Zakat dan Wakaf, 2024)
The obligation of zakat fitrah has social, economic, and spiritual aspects that are very important in the lives of Muslims. The management of zakat fitrah in amil zakat institutions is vital. The efficient and transparent collection, management, and distribution of zakat fitrah is an important factor in ensuring maximum benefits for beneficiaries. This study aims to explore the practice of managing zakat fitrah in an amil zakat institution with institutions, policies, and implementation. This research is descriptive qualitative with research methods that use observation and interviews. Research is descriptive and tends to use inductive analysis. The process of collecting Zakat Fitrah at LAZ ALMADINA is involved in publication and socialization to the community. LAZ ALMADINA holds regular recitations every Monday night at their location. The mechanism for distributing Zakat Fitrah to Eligible Recipients is carried out from various segments of society, including pilgrims and residents who attend the recitation. Kewajiban zakat fitrah memiliki aspek sosial, ekonomi, dan spiritual yang sangat penting dalam kehidupan umat Islam. Pengelolaan zakat fitrah di lembaga amil zakat menjadi hal yang vital. Penelitian ini bertujuan untuk mendalami praktik pengelolaan zakat fitrah di suatu lembaga amil zakat dengan kelembagan, kebijakan, dan implementasi. Penelitian ini adalah kualitatif deskriptif dengan metode penelitian yang menggunakan observasi dan wawancara. Penelitian bersifat deskriptif dan cenderung menggunakan analisis induktif. Proses pengumpulan Zakat Fitrah di LAZ ALMADINA terlibat dalam publikasi dan sosialisasi kepada masyarakat. LAZ ALMADINA menyelenggarakan pengajian rutin setiap malam Senin di lokasi mereka. Mekanisme pendistribusian Zakat Fitrah Kepada Penerima yang Memenuhi Syarat dilakukan dari berbagai segmen masyarakat, termasuk jamaah dan warga yang mengikuti pengajian.